UNVEILING SIADH: A CASE REPORT OF HYPONATREMIA SECONDARY TO ABIRATERONE THERAPY - Othman, Siti Nabilah Atiqah; Kum, Yik Zhi; Latib, Adilah Zulaikha Abd; Ng, Ooi Chuan (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hyponatremia is an uncommon complication of abiraterone treatment with an incidence rate of 0.4%-5%. Syndrome of inappropriate antidiuretic hormone secretion (SIADH) as a complication of abiraterone therapy is even rarer, and to our knowledge, this is the first-ever report on abirateroneinduced SIADH in a patient with metastatic hormonesensitive prostate cancer (mHSPC). CASE An 83-year-old Chinese male with newly diagnosed mHSPC presented acutely confused and lethargic with symptomatic hyponatremia (serum sodium of 126 mmol/L) following two weeks of oral abiraterone 1 g daily. The trial of intravenous fluids appeared to worsen hyponatremia, whereby serum sodium dropped further to 117 mmol/L. His vital signs were otherwise stable, with serum potassium, urea, creatinine, glucose, thyroid function and other electrolytes within normal range. His urine sodium was 138 mmol/L, urine osmolality was 259 mOsm/kg, serum osmolality was 259 mOsm/kg, and early morning serum cortisol was 396 nmol/L. Contrast-enhanced CT scan of the brain ruled out intracranial lesions or brain metastasis. Diagnosis of SIADH was made and the patient was put on fluid restriction. Within 4 days, his serum sodium improved to 125 mmol/L. Abiraterone was withheld and was subsequently discontinued. CONCLUSION Abiraterone is a selective, irreversible androgen biosynthesis inhibitor used for the treatment of metastatic prostate cancer and it has shown to improve the rate of overall survival. The prevalence of SIADH among patients receiving abiraterone therapy is not well established and the exact mechanism by which abiraterone induces SIADH remains elusive. It is hypothesized that abiraterone’s inhibition of CYP17A1, an enzyme crucial for androgen synthesis, may lead to dysregulation of ADH release, subsequently giving rise to SIADH. Further research is needed to fully understand this relationship. Prompt recognition and management of abiraterone-induced SIADH are crucial to prevent associated complications.